Effect of various operating conditions on the performance of photovoltaic module / Mohammad Mafizur Rahman - Mohammad Mafizur , Rahman (2016)
Photovoltaic (PV) modules are among the most effective, sustainable, and eco-friendly systems. A small portion of the incident solar radiation on a PV module is converted into electricity, whereas the remaining portion generates heat on the PV module layer, and consequently, decreases the output performance and efficiency of the module. Effective cooling systems can save energy and increase the performance of PV modules. In this study, various irradiation levels were applied to a PV module under indoor conditions to observe the temperature effects. A heat exchanger device was installed on the back of the module. Water flowed through the heat exchanger and radiator to cool the monocrystalline PV module. Results show that, under indoor conditions and without cooling, the total output power decreases by 20.47 W, and electrical efficiency decreases by 3.13% when solar temperature increases by 43.12 °C at 1000 W/m2 irradiation level. This output performance is 41.03% lower than the initial output performance and equivalent to a decrease of approximately 0.47 W in output power and 0.07% in electrical efficiency per 1 °C increase in solar cell temperature. For every 100 W/m2 increase in irradiation intensity, output power increases by 2.94 W with a 4.11 °C increase in solar cell temperature. Indoors, a 17.21 °C reduction in solar cell temperature increases output power by 8.04 W and electrical efficiency by 1.23%, thereby producing output power and efficiency that are 27.33% higher than those without cooling condition. The outdoor investigation shows that, without cooling, electrical efficiency decreases by 5.82% with a 26.10 °C increase in solar cell temperature during peak operating hours, thereby resulting in an output efficiency that is 43.83% lower than the initial output efficiency. Thus, electrical efficiency decreases by approximately 0.22% per 1 °C increase in solar cell temperature. For every 100 W/m2 increase in irradiation intensity, output power increases by 3.14 W with a 3.82 °C increase in solar cell temperature. Outdoors, reducing solar cell temperature by 10.28 °C increases output power by 7.64 W and electrical efficiency by 1.17%, thereby resulting in an increase of 15.72% in both performance parameters with respect to those without cooling condition. Output power decreases by approximately 3.16 W with an increase of 20% in relative humidity (RH), and is reduced by 7.70 W because of dust deposition on the surface of the indoor solar module. A decrease of approximately 1.6% in output efficiency occurs with an increase of 12.10% in RH, and this parameter decreases by 1.34% because of dust deposition on the surface of the outdoor solar module. Therefore, parameters such as solar cell temperature, irradiation intensity, cooling fluid mass flow rate, humidity, and dust influence PV module performance. Water cooling can be applied in large-capacity PV power generation plants located in tropical or hot-climate areas with exiguity of natural water resources. Different configurations of the heat exchanger device to cool PV modules, and consequently, improve performance can be considered in future studies.